Pain in Advanced Stages of Dementia: The Perspective of Medical Students - Neumann-Podczaska, Agnieszka (Medicina (Kaunas), 2019)
Background and objective: The number of studies related to medical students’ attitude toward pain is limited. The aim of our study was, thus, to assess the medical students’ knowledge of pain assessment and treatment in advanced stages of dementia in order to improve the existing curriculum in this area. Material and methods: We analyzed the medical students’ knowledge about pain in advanced dementia based on a short questionnaire. The research was anonymous. The questionnaire was completed by 147 students. Results: The students most often suggested that pain in patients with advanced dementia could be manifested via body language and facial expression (107 students—72.8% and 100 students—68.0%, respectively). Vocalization was the third most frequently reported pain manifestation (84–57.1%). Other groups of pain symptoms (changes in activity patterns, changes in interpersonal interactions, and mental status changes) were indicated less often (p < 0.0001). Only five students (3.4%) listed the DOLOPLUS behavioral pain scale as an assessment tool for patients with advanced dementia, and 16 (10.9%) indicated observational scale elements or a necessity to observe the patient. Still, 110 students (74.5%) correctly characterized pain treatment in patients with advanced dementia. Conclusions: To the best of our knowledge, our study is pioneering in defining the deficits of medical students’ knowledge on pain assessment and treatment in patients with advanced dementia. We highlighted knowledge gaps in the area of pain assessment which might make medical students incapable of proper pain treatment. Following the International Association for the Study of Pain considerations regarding the need for excellence in pain education, these results can contribute to the improvement of existing medical curricula in Poznan University of Medical Sciences to include pain management in dementia in a more ”patient-centered” way in order to increase future staff’s competency and to assure a better quality of care.